Analysis ANALISIS AKTIVITAS PEMBELAJARAN DARING MAHASISWA PENDIDIKAN EKONOMI FKIP: Learning Activities - NASMAL HAMDA; Ade Holisoh (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to obtain information about the online learning activities of FKIP Economics Education students which are carried out at Pamulang University every semester. The research method used in this study is a descriptive method in the form of a survey. In addition, the use of Google Forms for data collection using indirect communication is carried out in this study. There were 54 student respondents who were surveyed consisting of Regular A and B Semester Economics Education students at Pamulang University. The results of the study show that online learning provided by students is "good enough" considering various considerations and with all the problems and constraints that exist. It is hoped that in the future online learning can be used as an assessment and online learning experience carried out by both students and lecturers at Pamulang University. There were 54 student respondents who were surveyed consisting of Regular A and B Semester Economics Education students at Pamulang University. The results of the study show that online learning provided by students is "good enough" considering various considerations and with all the problems and constraints that exist. It is hoped that in the future online learning can be used as an assessment and online learning experience carried out by both students and lecturers at Pamulang University.